The distribution of the macro-zoobenthos community based on the characteristics of the mangrove sediments in Aceh Besar. Issue 1 (February 2021) - Sari, I P; Sarong, M A; Rusdi, M; Deli, A; Irham, M
Abstract: Spatially, the composition of mangrove vegetation and macro-zoobenthos varies due to the characteristics of the sediment substrate in mangrove area. Therefore, the purpose of this study is to analyse the elements contained in the sediments in the mangrove area and to identify macro-zoobenthos species based on the characteristics of the sediment subtract in Peukan Bada and Baitussalam of Aceh Besar district. The method used in this research is the coring method for sediment sampling, while the sediment characteristics analysis was carried out by the sieve method. For the presence of mangroves, the transect method is applied and analysed based on the identification of mangrove species characteristics in the laboratory. Meanwhile, macro-zoobenthos were collected based on mangrove density using hand grabs and sieved at a size of 0.5 mm, then analysis of the dominance and partial correlation between the sediments of the mangrove area and the presence of macro-zoobenthos was carried out. The results show that 89% of the substrate is a muddy fine sand sediment with the dominance of the mangrove species Rhizopora mucronate and Sonneratia alba species. The dominance level of macro-zoobenthos is in the low to high category with a dominance value of 0.47 - 0.88. Furthermore, the partial correlation test for mangroves, macro-zoobenthos and sediment showed that there was a strong relationship between them.